Employee-driven Innovation in Welfare Services - Wihlman, Thomas; Hoppe, Magnus; Wihlman, Ulla; Sandmark, Hélène (Nordic Journal of Working Life Studies, 2014)
There is a growing interest in both employee-driven innovation (EDI) and innovation in welfare services, but a lack of empirical studies addressing innovation from the employee perspective. Accordingly, this study was designed to contribute with well-grounded empirical knowledge, aiming to explore the barriers to and opportunities for participation in innovation experienced by employees of the Swedish welfare services. In order to reach the aim, a qualitative thematic analysis of 27 semi-structured interviews with employees in four municipalities was performed. The study identified three main themes, with a great impact on the innovative performance of the studied organizations: support, including leadership and innovation processes; development, including creativity and learning; and organizational culture, which includes attitudes and communication, all essential ingredients in EDI. Experienced barriers for innovation were unclear or non-existing innovation processes with ambiguous goals, insufficient learning, and deficient organizational slack, thus creating a tension between day-to-day work and innovation and hindering reflection and exploration. Attitudes of colleagues and lack of communication were also barriers to implementing innovation, suggesting the need for better management support for a communicative and open culture. Opportunities were found, including commitment to innovation and willingness to try new ideas, but the employees must be given the mandate and sufficient time to develop the potential that emerges from continuous learning, time for reflection, and user dialogue. The conclusion was that incremental innovations existed, but the full potential of these did not benefit the entire organization due to inadequate communication and lack of innovation processes. The study improves our understanding of how employees regard their involvement in innovation. It also discusses how to make better use of employees’ resources in innovation processes and contributes to important knowledge about EDI in the public sector. On the basis of our results, we suggest a model of EDI for use in practice.